Study of Quality of Work Life (QWL) - G Nasl Saraji; H Dargahi (Tehran University of Medical Sciences, 2006)
A high quality of work life (QWL) is essential for organizations to continue to attract and retain employees. QWL is a comprehensive program designated to improve employee satisfaction. This research aimed to provide insights into the positive and negative attitudes of Tehran University of Medical Sciences (TUMS) Hospitals' employees from their quality of life. A cross- sectional, descriptive and analytical study was conducted among 908 TUMS hospitals' employees by questionnaire at 15 studied hospitals. A stratified random sampling technique was used to select respondents as nursing, supportive and paramedical groups. The results showed that the majority of employees were dissatisfied with occupational health and safety, intermediate and senior managers , their income, balance between the time they spent working and with family and also indicated that their work was not interesting and satisfying. TUMS hospitals' employees responding to this survey have a poor quality of work life. We suggest more training and educations for TUMS hospitals' managers on QWL issues are planned.